2012
DOI: 10.1371/journal.pone.0037864
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Kaiso Expression Is Associated with High Grade and Triple-Negative Invasive Breast Cancer

Abstract: Kaiso is a BTB/POZ transcription factor that is ubiquitously expressed in multiple cell types and functions as a transcriptional repressor and activator. Little is known about Kaiso expression and localization in breast cancer. Here, we have related pathological features and molecular subtypes to Kaiso expression in 477 cases of human invasive breast cancer. Nuclear Kaiso was predominantly found in invasive ductal carcinoma (IDC) (p = 0.007), while cytoplasmic Kaiso expression was linked to invasive lobular ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 59 publications
4
72
1
1
Order By: Relevance
“…Recent studies in cancer have examined localization of Kaiso in relation to p120. Overall, they indicated that nuclear Kaiso localization is decreased when p120 resides in the cytosol, although it appeared that the expression of Kaiso and its localization are highly variable, and depend on the cellular context and type of tumor examined (Soubry et al, 2005;Kantidze et al, 2009;Soubry et al, 2010;Zhang et al, 2011;Vermeulen et al, 2012). Notwithstanding this high variability, several bona fide Kaiso targets (e.g.…”
Section: The Role Of Kaiso In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in cancer have examined localization of Kaiso in relation to p120. Overall, they indicated that nuclear Kaiso localization is decreased when p120 resides in the cytosol, although it appeared that the expression of Kaiso and its localization are highly variable, and depend on the cellular context and type of tumor examined (Soubry et al, 2005;Kantidze et al, 2009;Soubry et al, 2010;Zhang et al, 2011;Vermeulen et al, 2012). Notwithstanding this high variability, several bona fide Kaiso targets (e.g.…”
Section: The Role Of Kaiso In Cancermentioning
confidence: 99%
“…Another possibility is that repression of currently unknown Kaiso targets might promote tumor formation. In favor of this hypothesis is the fact that the presence of nuclear Kaiso correlates with metastatic prostate cancer and high-grade invasive ductal carcinoma (IDC), suggesting that Kaiso-mediated transcriptional repression indeed exerts oncogenic properties (Jones et al, 2012;Vermeulen et al, 2012). By contrast, non-small-cell lung cancer (NSCLC) and ILC cells show reduced levels and/or cytosolic localization of Kaiso, a p120-catenin in cancer 3519 finding that is in line with the assumption that Kaiso represses the expression of oncogenic proteins (Dai et al, 2011;Vermeulen et al, 2012).…”
Section: The Role Of Kaiso In Cancermentioning
confidence: 99%
“…Analyses on human samples were conducted as described previously (28). For analysis of growth pattern and metastasis formation, Fisher exact test was used.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Our results showed that in addition to stabilizing E-cadherin and b catenin, MUC1 and p120 catenin together caused significant effects on the transcription of Wnt target genes, including cyclin D1, which were distinct in the absence of either p120 catenin or MUC1. For cyclin D1, MUC1 and p120 catenin bound to and stabilized b catenin in the cell and at the cyclin D1 promoter; they also bound and caused de-repression of Kaiso, a transcriptional repressor known to be targeted by p120 catenin, 10 which together led to high levels of transcription of cyclin D1. High activity of the cyclin D1 promoter and elevated cyclin D1 protein also significantly increased cell proliferation.…”
Section: Introductionmentioning
confidence: 99%